4CPS-122 Overview of the impact of penicillin allergy labels on antibiotic use in the emergency department. (23rd March 2022) - Garreta, G; Meca, N; Sebastian, C; Iglesias, M; Salazar, F; Pardo, J; Nicolas, J
Abstract : Background and importance: Many patients claim to be allergic to penicillin (Pen-A); however, only 10–25% of these are truly penicillin-allergic. It needs to be established if they are truly allergic (type-1 allergy) in order to to indicate alternative antibiotics. Moreover, patients who do not have a type-1 allergy can safely receive cephalosporins or carbapenems, but having a label of Pen-A may be associated with prescription of broad-spectrum antibiotics (BSA), hospital stay duration and readmission. Aim and objectives: Assess the impact of Pen-A labels on antibiotic in an emergency department (ED). Identify patients who remain appropriate candidates to receive beta-lactam therapy or cephalosporins, are mislabelled or may be dis-labelled with penicillin allergy skin testing (PST). Material and methods: Retrospective cohort study with ED cases treated with BSA from January 2020–January 2021. Pen-A were identified by assessing all allergies in the electronic medical record. Each patient with a Pen-A label was matched for age, gender, BSA prescribed in ED and previous exposures to penicillin or cephalosporins. PST may be considered if they meet any of the criteria recommended: history of Pen-A >10 years ago, frequent antibiotic use required, immunosuppressed state and history of infections caused by multidrug-resistant (MDR) bacteria. Results: A total of 287 patients (mean age 62 years; SD 16 years; 53% men) were enrolled. The main antibiotic prescribed in Pen-A patients were quinolones (49%) and macrolides/lincosamides (21%). In 88% cases, antibiotic hospital guides suggested treatments with a cephalosporin. Of 46 patients with Pen-A, 24 had non-type 1/non-severe reaction, 6 type 1 allergy/severe reaction, 4 without reaction (mislabelled) and 12 not documented. 37(80.4%) patients were treated previously with cephalosporins, whereas only 2 patients presented cross-reactivity. 30 (65.2%) patients met criteria to consider referring to PST, of which 67% had history of Pen-A >10 years ago, 60% required frequent antibiotic use, 13% were immunosuppressed and 9% had infections caused by MDR bacteria. Conclusion and relevance: Most patients, around 80% would have been spared the use of BSA if the Pen-A label had been assessed. Furthermore, most patients who had received cephalosporins did not have cross-reactivity. The introduction of PST could help correctly verify Pen-A in 65.2% patients. Hereinafter, ED pharmacist will be prepared to evaluate possible Pen-A to reduce the use of BSA and de-label when necessary. References and/or acknowledgements: Conflict of interest: No conflict of interest